The Potential for Lunar and Martian Regolith Simulants to Sustain Plant Growth: A Multidisciplinary Overview - Duri, Luigi Giuseppe; Caporale, Antonio Giandonato; Rouphael, Youssef; Vingiani, Simona; Palladino, Mario; De Pascale, Stefania; Adamo, Paola (Frontiers in Astronomy and Space Sciences, 2022)
Bioregenerative life support systems (BLSS) are conceived of and developed so as to provide food sources for crewed missions to the Moon or Mars. The in situ resource utilization (ISRU) approach aims to reduce terrestrial input into a BLSS by using native regoliths and recycled organic waste as primary resources. The combination of BLSS and ISRU may allow sustainable food production on Moon and Mars. This task poses several challenges, including the effects of partial gravity, the limited availability of oxygen and water, and the self-sustaining management of resources. Lunar and Martian regoliths are not available on Earth; therefore, space research studies are conducted on regolith simulants that replicate the physicochemical properties of extra-terrestrial regoliths (as assessed in situ by previous missions). This review provides an overview of the physicochemical properties and mineralogical composition of commercially available Lunar and Martian regolith simulants. Subsequently, it describes potential strategies and sustainable practices for creating regolith simulants akin to terrestrial soil, which is a highly dynamic environment where microbiota and humified organic matter interact with the mineral moiety. These strategies include the amendment of simulants with composted organic wastes, which can turn nutrient-poor and alkaline crushed rocks into efficient life-sustaining substrates equipped with enhanced physical, hydraulic, and chemical properties. In this regard, we provide a comprehensive analysis of recent scientific works focusing on the exploitation of regolith simulant-based substrates as plant growth media. The literature discussion helps identify the main critical aspects and future challenges related to sustainable space farming by the in situ use and enhancement of Lunar and Martian resources.